Natural Radioactivity and the Evaluation of Related Radiological Risks in Concrete Used in Prizren District, Kosovo - M. Qafleshi; M. K. Xhixha; G. Nafezi; D. Kryeziu; D. Qafleshi (Atom Indonesia, 2021)
This study aims to investigate the natural radioactivity levels in concrete made of Portland cement and used in Prizren district, Republic of Kosovo. The activity concentrations of 40K, 226Ra and 232Th were determined by gamma-ray spectroscopy technique with High Purity Germanium (HPGe) detector. The activity concentrations of 40K, 226Ra, and 232Th were found to be 15.4-28.4 Bq kg-1, 4.3-5.9 Bq kg-1 and 2.0-4.1 Bq kg-1, respectively. These results were used to calculate the activity concentration index as recommended by the Basic Safety Standard of Council Directive 2013/59/EURATOM for the safe use of building material. Kosovo must comply with this recommendation in the framework of legislative harmonization with the European Union. The activity concentration index was found to be lower than the reference level of unity (I=0.05), corresponding to an annual effective dose rate of AED=0.05 mSv y-1. The concentration of radionuclides and radiological hazard parameters for concrete investigated in this study were compared with respective results found in literature from different countries. These results show very low activity concentrations, indicating that concrete used in Prizren, Kosovo, does not pose any significant risk due to its use as building material.